2015
DOI: 10.1186/s12885-015-1090-7
|View full text |Cite
|
Sign up to set email alerts
|

Radiosensitization with combined use of olaparib and PI-103 in triple-negative breast cancer

Abstract: BackgroundTriple-negative breast cancer (TNBC) shows aggressive clinical behavior, but the treatment options are limited due to lack of a specific target. TNBC shares many clinical and pathological similarities with BRCA-deficient breast cancer, for which poly(ADP-ribose) polymerase (PARP) inhibitor is effective, but PARP inhibitor alone failed to show clinical effects in patients with sporadic TNBC. Radiation induces DNA double-strand breaks, and the phosphoinositide 3-kinase (PI3K) signaling pathway has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 28 publications
(43 reference statements)
1
33
0
Order By: Relevance
“…In addition, PI-103 can radiosensitize prostate [34], colorectal [35] and breast [36, 37] cancer cells alone or in a combination with a PARP inhibitor olaparib [37]. …”
Section: Discussionmentioning
confidence: 99%
“…In addition, PI-103 can radiosensitize prostate [34], colorectal [35] and breast [36, 37] cancer cells alone or in a combination with a PARP inhibitor olaparib [37]. …”
Section: Discussionmentioning
confidence: 99%
“…Many preclinical and clinical studies have been performed to determine RT response in different molecular subtypes of breast cancer, and sensitivity to radiation seems to be higher in hormone-positive tumors as compared to that of HER2-type or TNBC [6]. To enhance the effects of RT in TNBC, several agents have been investigated in preclinical studies [5,7]. Cell cycle checkpoints are often deregulated in cancer cells, and thus, have been used as therapeutic targets.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, radiation was used by Jang et al, to induce the burden of DNA DSBs. They reported that radiosensitization with combined use of olaparib and PI-103 has found to be efficacious in a xenograft model of TNBC [70]. Efficacy of carboplatin alone and in combination with ABT888 in Intracranial murine models of BRCA-mutated and BRCA-wild-type TNBC is also reported by Karginova et al [76].…”
Section: Parp Inhibitors As Chemo/radiopotentiating Agents: Tnbc and mentioning
confidence: 76%